The English girl [compact disc, unabridged] - Silva, Daniel, 1960- (Silva, Daniel, 1960- Gabriel Allon series., 2013)
When a young British woman vanishes on the island of Corsica, a prime minister's career is threatened with destruction. Gabriel Allon, master art restorer, spy, and assassin, is thrust into a game of shadows where nothing is what it seems, and the only thing more dangerous than his enemies might be the truth.